Smart specialization concept and its implication for regional development in non-eu countries - Gryga, Vitalii (Universidad Autónoma de Chiriquí, 2021)
The main objective of this research is to analyze the smart specialization approach of the European Union and the innovation policy approach of China. Through an analysis of publications, as well as official documents of the European Community, it was possible to identify milestones and key factors that influenced innovation policy in Europe. Smart specialization is a place-based approach, which means that it draws on the assets and resources available to regions and Member States and their specific socio-economic challenges to identify unique opportunities for development and growth (JRC, 2018).The study analyzes the challenges Ukraine faced in the first stage of smart implementation of specialization, such as misunderstanding of the concept by different Ministries, low innovation policy creation capacities, lack of relevant data and lack of will. of the business sector. At the same time reviewing the concept of specialization in China deducing that there is a certain degree of overlap of specific industries in the provinces. The provinces tend to choose between as many priorities as possible and this can lead to duplication of efforts, contradicting the idea of smart specialization. Therefore, greater coordination between the provinces is needed to better explore their strengths and improve the allocation of money in R&D and innovation infrastructure and to achieve more synergies in China's development. The research concludes that one of the key points of the smart specialization process is the enterprise discovery process. However, implementing smart specialization throughout the European region reveals challenges for many less developed regions, which lack excellent research facilities and the necessary skills.